A Co / Cu-MOFs material preparation method and application

By introducing cobalt ions and foam copper in the preparation process of Co/Cu-MOFs materials, and regulating the electronic structure and Cu-O bond length of the material by hydrothermal reaction and annealing treatment, the problem of insufficient oxygen activation in VOCs degradation is solved, and efficient VOCs removal effect is achieved.

CN118719152BActive Publication Date: 2025-03-04HUAIYIN TEACHERS COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410807929.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-21
Publication Date
2025-03-04
Estimated Expiration
2044-06-21

AI Technical Summary

Technical Problem

The electronic structure cannot be accurately regulated during the preparation of existing Co/Cu-MOFs materials, and the activation of molecular oxygen is not sufficient during the degradation of VOCs.

Method used

By dispersing the cobalt ion precursor and the organic ligand in an organic solvent, adding foam copper for hydrothermal reaction, Co-supported Cu-based MOFs material was obtained, and then annealed to prepare Co/Cu-MOFs material. This method can regulate the bandwidth of CuO and Cu-O bond length, improve the absorption of visible light and activation of molecular oxygen.

Benefits of technology

The multi-stage pore structure and large specific surface area of ​​Co/Cu-MOFs materials are realized, which improves its degradation efficiency of VOCs, especially the removal effect of volatile organic pollutants under light is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118719152B_ABST
    Figure CN118719152B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a Co / Cu-MOFs material and an application thereof, and belongs to the field of environmental catalysis technology. The method for preparing the Co / Cu-MOFs material comprises: dispersing a cobalt ion precursor and an organic ligand in an organic solvent, then adding copper foam, and performing a hydrothermal reaction. The product of the hydrothermal reaction is washed, centrifuged and dried to obtain a Co-loaded Cu-based MOFs material, which is annealed to obtain the Co / Cu-MOFs material. The Co / Cu-MOFs material is used to treat volatile organic pollutants under light. Compared with the prior art, the Co / Cu-MOFs material of the present invention has a large surface area, a multi-level pore structure, and the doping of single-atom Co can accurately control the electronic structure of the carrier, thereby effectively improving the catalyst's absorption of visible light and its ability to activate molecular oxygen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental catalysis, and in particular relates to a preparation method and application of a Co / Cu-MOFs material. Background Art

[0002] In recent years, with the progress of science and technology and the rapid development of human society, the process of industrialization has continuously reached a new level. Although the control of environmental pollution has become increasingly strict during the development process, with the annual increase in resource and energy consumption, the emission of volatile organic compounds (VOCs) has been increasing year by year, which has seriously threatened the safety of the atmospheric ecological environment and human health. Based on the advantages of low energy consumption and low cost of photocatalysis, VOCs can be directly oxidized into carbon dioxide, water or small molecules, which can effectively reduce their harm to the ecological environment and human health, and has a good application prospect in the field of atmospheric pollution control.

[0003] Co / Cu-MOFs materials are materials with specific properties obtained by converting MOFs through certain transformation treatments, such as heat treatment and chemical treatment. These derivatives not only retain some of the original characteristics of MOFs (high specific surface area, porosity, etc.), but also have increased stability and enhanced conductivity. By regulating the diversification of MOFs structures to change their electronic structures, their adsorption and activation capabilities for VOCs molecules can be adjusted. Therefore, Co / Cu-MOFs materials have potential application prospects in the field of VOCs removal. Rational design and controllable regulation of the nanostructure of Co / Cu-MOFs materials to achieve optimization of their performance are the key to promoting their practical application and industrialization. At present, international research on the structural regulation of Co / Cu-MOFs materials is not in-depth, especially in terms of precise control of electronic structure, activation of active oxygen and high stability, which still face great challenges. Summary of the invention

[0004] In order to solve the following problems existing in the prior art: 1) the electronic structure of the Co / Cu-MOFs material preparation process cannot be precisely controlled; 2) the activation of molecular oxygen in the process of degrading VOCs is not yet sufficient, the present invention proposes a Co / Cu-MOFs material preparation method and application. The present invention provides a simple, low-cost, and structurally adjustable Co / Cu-MOFs material preparation method in view of the defects and market demands of the current Co / Cu-MOFs material structure control, precise control of chemical state, and performance optimization technologies.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] The present invention provides a method for preparing a Co / Cu-MOFs material, comprising the following steps:

[0008] The cobalt ion precursor and the organic ligand are dispersed in an organic solvent, and then copper foam (CF) is added to carry out a hydrothermal reaction. The product of the hydrothermal reaction is washed, centrifuged and dried to obtain a Co-loaded Cu-based MOFs material;

[0009] The Co-loaded Cu-based MOFs material is annealed to obtain the Co / Cu-MOFs material.

[0010] Preferably, in the Co / Cu-MOFs material preparation method, the molar ratio of the cobalt ion precursor to the organic ligand is (0.5-3): (0.5-2).

[0011] In the present invention, the incorporation of Co can regulate the bandgap width of CuO, promote the absorption of visible light and the transfer of photogenerated electrons. In addition, due to the incorporation of Co, it can replace part of the oxygen element in CuO, change the bond length of Cu-O and the coordination relationship of Cu, thereby regulating the valence state of Cu and the covalency of Cu-O. Co regulates the covalency of Cu-O and thereby reduces the interfacial electron transfer energy to promote the adsorption of oxygen molecules, and activates O2 from a stable ground state to a high-energy state active oxygen activation, thereby improving the degradation efficiency of organic pollutants.

[0012] Preferably, in the Co / Cu-MOFs material preparation method, the cobalt ion precursor is cobalt nitrate hexahydrate or cobalt chloride hexahydrate.

[0013] Preferably, in the Co / Cu-MOFs material preparation method, the organic ligand is terephthalic acid.

[0014] Preferably, in the Co / Cu-MOFs material preparation method, the organic solvent includes at least one of N,N-dimethylformamide, methanol and ethanol.

[0015] Preferably, in the Co / Cu-MOFs material preparation method, the size of the copper foam is (100-250 mm)*(200-400)*(1-2 mm) (referring to the sizes of length, width and thickness, respectively).

[0016] More preferably, the copper foam is clean copper foam, and the pretreatment of the copper foam is: first, treating the copper foam with 1 mM hydrochloric acid solution for 15 minutes to remove oxides on the surface, then immersing the copper foam in acetone solution and ultrasonically treating it for 15 minutes to remove organic matter on the surface, and finally ultrasonically treating it in ethanol and pure water for 15 minutes respectively to obtain clean copper foam.

[0017] Preferably, in the Co / Cu-MOFs material preparation method, the temperature of the hydrothermal reaction is 120 to 150° C., and the insulation time is 10 to 20 hours.

[0018] Preferably, in the Co / Cu-MOFs material preparation method, the annealing temperature is 200-400° C., the heating rate is 2-5° C. / min, the holding time is 2-5 h, and the annealing atmosphere is air.

[0019] The second technical solution of the present invention:

[0020] The present invention also provides a Co / Cu-MOFs material prepared according to the above method. The Co / Cu-MOFs material obtained by the present invention is a layered nanosheet. The Co / Cu-MOFs material of the present invention has a large specific surface area and a multi-level pore structure, and the doping of single-atom Co can accurately control the electronic structure of the carrier, thereby effectively improving the catalyst's absorption of visible light and its ability to activate molecular oxygen.

[0021] The third technical solution of the present invention:

[0022] The present invention also provides application of the Co / Cu-MOFs material in treating volatile organic pollutants under light.

[0023] Preferably, the volatile organic pollutants include toluene, chlorobenzene, ethyl acetate, acetone, tetrahydrofuran, cyclohexane, and styrene.

[0024] Preferably, the Co / Cu-MOFs material is used to remove volatile organic compounds (VOCs) in the air, and the specific process includes: taking the Co / Cu-MOFs material, mixing it with volatile organic compounds (VOCs), and performing a degradation reaction.

[0025] Preferably, the Co / Cu-MOFs material is added in an amount of (100-250 mm)*(200-400)*(1-2 mm) per 250 mL of volatile organic pollutants.

[0026] Preferably, when treating volatile organic pollutants under light, the relative humidity of the air is 25% to 75%.

[0027] More preferably, the Co / Cu-MOFs material is used to remove toluene from the air, and the initial concentration of toluene is 100 ppm to 300 ppm.

[0028] Compared with the prior art, the present invention has the following advantages and technical effects:

[0029] (1) The Co / Cu-MOFs material prepared by the present invention has a multi-level pore structure, has the advantages of large specific surface area, porosity, high conductivity, etc., can efficiently degrade VOCs, and has great application potential in the field of catalysis;

[0030] (2) Single-atom Co can precisely regulate the valence state of the carrier Cu. As the amount of Co added increases, the valence state of Cu changes.

[0031] (3) The modification of transition metal Co increases the excellent photoresponse to visible light. On the other hand, an electron transfer channel is formed between Co and CuO / CF support, which further prolongs the O-O bond of adsorbed O2, leading to the rapid dissociation of O2 and the subsequent generation of ROS, thus promoting the deep oxidation of aromatic pollutants.

[0032] (4) The chemical reagents used in the present invention are all commonly used reagents, which are cheap and easily available. The process of preparing Co / Cu-MOFs materials in the present invention is convenient, highly repeatable and highly controllable. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0034] Figure 1 This is a scanning electron microscope (SEM) photograph of 1CoCuO / CF synthesized in Example 1;

[0035] Figure 2 This is a SEM photo of the CuO / CF synthesized in Comparative Example 1;

[0036] Figure 3 X-ray diffraction spectra (XRD) of 1CoCuO / CF synthesized in Example 1 and CuO / CF synthesized in Comparative Example 1;

[0037] Figure 4 The UV-Vis diffuse reflectance spectra (UV-Vis) of 1CoCuO / CF synthesized in Example 1 and CuO / CF synthesized in Comparative Example 1 are shown;

[0038] Figure 5 The photocatalytic degradation diagram of 1CoCuO / CF synthesized in Example 1 and CuO / CF synthesized in Comparative Example 1;

[0039] Figure 6 This is the activity diagram of the photocatalyst 1CoCuO / CF in Example 1 for photocatalytic degradation of organic pollutants other than toluene. DETAILED DESCRIPTION

[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0041] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0045] Unless otherwise specified, the room temperature in the embodiments of the present invention is 25±2°C.

[0046] In the embodiments of the present invention, unless otherwise specified, conventional processing techniques in the art are used.

[0047] All raw materials used in the embodiments of the present invention are commercially available.

[0048] In the embodiments of the present invention, the prepared products are characterized by the following means: X-ray diffraction measured on a Rigaku D / Max-RB X-ray diffractometer of Japan is used to analyze the structure of the sample; scanning electron microscope photos are obtained using a Hitachi S-4800 scanning electron microscope of Japan. The concentrations of toluene and CO2 during the experiment are detected by gas chromatography (GC9720, column flow rate 1mL / min, injection port temperature 250°C, column box temperature 160°C, FID detector temperature 280°C) and photogenerated spectrometer (DKG-ONE).

[0049] The technical solution of the present invention is further illustrated by the following embodiments.

[0050] Example 1

[0051] The preparation method of Co / Cu-MOFs material is as follows:

[0052] (1) Pretreatment of copper foam: First, copper foam (CF, 200 mm*400 mm*1.5 mm) was treated with 1 mM hydrochloric acid solution for 15 min to remove oxides on the surface. Then, CF was immersed in acetone solution and ultrasonically treated for 15 min to remove organic matter on the surface. Finally, CF was ultrasonically treated in ethanol and pure water for 15 min, respectively, to obtain clean CF. The clean CF was dried in a vacuum at 60 °C for 12 h to obtain clean CF.

[0053] (2) Preparation of CoCu-MOFs / CF by hydrothermal method: At room temperature, cobalt nitrate hexahydrate and terephthalic acid were dissolved in 50 mL of N,N-dimethylformamide and stirred for 30 min to obtain a solution in which the concentration of cobalt nitrate was 1.0 mM and the concentration of terephthalic acid was 2 mM. Then, the above solution was transferred to a 100 mL polytetrafluoroethylene-lined reactor containing clean CF and kept in an oven at 120 ° C for 12 h. After cooling to room temperature, the obtained sample was washed three times with N,N-dimethylformamide and methanol. Finally, CoCu-MOFs / CF was obtained by drying at 80 ° C for 12 h. In this example, the Co content was 1 mM, marked as 1CoCu-MOFs / CF.

[0054] (3) The CoCu-MOFs / CF obtained above was annealed at 300°C with a heating rate of 2°C / min and a holding time of 3h in an air atmosphere to obtain a Co / Cu-MOFs material, which was recorded as 1CoCuO / CF.

[0055] Example 2

[0056] The same as Example 1, except that the concentration of Co(NO3)2·6H2O is 0.10 mM, and the obtained Co / Cu-MOFs material is marked as 0.1CoCuO / CF.

[0057] Example 3

[0058] The same as Example 1, except that the concentration of Co(NO3)2·6H2O is 0.50 mM, and the obtained Co / Cu-MOFs material is marked as 0.5CoCuO / CF.

[0059] Example 4

[0060] The same as Example 1, except that the concentration of Co(NO3)2·6H2O is 2.0 mM, and the obtained Co / Cu-MOFs material is marked as 2CoCuO / CF.

[0061] Example 5

[0062] The same as Example 1, except that the concentration of Co(NO3)2·6H2O is 3.0 mM, and the obtained Co / Cu-MOFs material is marked as 3CoCuO / CF.

[0063] Example 6

[0064] The same as Example 1, except that the concentration of CoCl2·6H2O is 0.2 mM, and the obtained Co / Cu-MOFs material is marked as 0.2CoCuO / CF-Cl.

[0065] Example 7

[0066] Same as Example 1, except that the temperature of the hydrothermal reaction is 150° C. and the holding time is 10 h.

[0067] Example 8

[0068] Same as Example 1, except that the temperature of the hydrothermal reaction is 120° C. and the holding time is 20 h.

[0069] Example 9

[0070] Same as Example 1, except that the annealing temperature is 200° C. and the holding time is 5 h.

[0071] Example 10

[0072] Same as Example 1, except that the annealing temperature is 400° C. and the holding time is 2 h.

[0073] Comparative Example 1

[0074] The same as Example 1, except that in step (2), no Co precursor was added, that is, no cobalt nitrate hexahydrate was added. The Co / Cu-MOFs material obtained in this comparative example is marked as CuO / CF.

[0075] CF is carefully selected as the matrix for photocatalysts due to its highly interconnected microporous structure, large surface area and fast electron transfer rate. Importantly, the surface metallic Cu species can be easily converted into Cu oxides by self-reconstruction, while the residual Cu skeleton can directly serve as an electron reservoir with high electronic conductivity. CF has a smooth surface and interconnected porous structure, which is conducive to the in situ growth of Cu-MOF on the CF surface. After solvothermal treatment, Cu-MOF / CF and CoCu-MOFS / CF were synthesized by the assembly of metals (Cu, Co) and organic ligands (terephthalic acid). Unlike the smooth surface of CF, the synthesized Cu-MOF with nanosheet structure is uniformly distributed in a vertical array on CF without shedding, indicating that the nanosheets can be attached to CF, the interfacial interaction force is enhanced, and the charge transfer is beneficial.

[0076] The scanning electron microscope (SEM) photo of 1CoCuO / CF synthesized in Example 1 is shown in Figure 1 It can be seen that 1CoCuO / CF maintains the highly interconnected microporous structure of copper foam.

[0077] The scanning electron microscope (SEM) photo of CuO / CF synthesized in Comparative Example 1 is shown in Figure 2 It can be seen that CuO / CF maintains the highly interconnected microporous structure of copper foam.

[0078] The X-ray diffraction spectra (XRD) of 1CoCuO / CF synthesized in Example 1 and CuO / CF synthesized in Comparative Example 1 are shown in Figure 3 It can be seen that the Cu in CuO / CF is +2 valence. After the introduction of Co, Cu changes to a low valence state. There is no obvious peak of Co element in the 1CoCuO / CF material, indicating that Co exists in the form of single atoms and is evenly dispersed.

[0079] The UV-Vis diffuse reflectance spectra (UV-Vis) of 1CoCuO / CF synthesized in Example 1 and CuO / CF synthesized in Comparative Example 1 are shown in FIG. Figure 4 The introduction of Co improves the absorption of visible light by CuO / CF.

[0080] Catalyst performance test:

[0081] The Co / Cu-MOFs materials prepared in Examples 1 to 5 and Comparative Example 1 were subjected to a catalytic degradation of toluene under simulated visible light (i.e., the Co / Cu-MOFs materials were used as photocatalysts to catalyze the degradation of toluene). The photocatalytic oxidation of VOCs was carried out in a homemade cylindrical quartz reactor (diameter: 50 mm, height: 100 mm). The specific experimental process is as follows: the air generator is divided into two paths, each connected to a mass flow controller, one path of air is passed into a reaction tank filled with deionized water to adjust the humidity of the reaction system, and the other path drives the toluene gas. The Co / Cu-MOFs material is placed in a photoreactor (the distance between the light and the catalyst: 60 mm). Open the gas path device, and after the humidity reaches the target value (relative humidity is 75%), close the gas path, seal the device, and place the reactor in a dark environment for 30 minutes to allow the adsorption and desorption of toluene to reach equilibrium. Then turn on the light source (xenon lamp, 300W, λ>420nm, optical density: 50mW / cm 2 ), condensed circulating water was introduced, and the same amount (1 mL) of toluene gas was taken every 3 minutes. The concentrations of toluene and CO2 during the experiment were detected by gas chromatography (GC9720) and photogenerated spectrometer (DKG-ONE). The initial concentration of toluene was 100 ppm, the size of the Co / Cu-MOFs material was 200 mm*400 mm*1.5 mm, and the reaction time was 18 minutes.

[0082] The photocatalytic degradation diagram of 1CoCuO / CF synthesized in Example 1 and CuO / CF synthesized in Comparative Example 1 is shown in FIG. Figure 5 It can be seen that under visible light, the degradation efficiency of 1CoCuO / CF for toluene is significantly improved compared with CuO / CF.

[0083] Figure 6 This is the activity diagram of the photocatalyst of Example 1 for degrading organic pollutants other than toluene (the degradation process of other organic pollutants is the same as that of toluene). It can be seen that 1CoCuO / CF also has a good degradation effect on pollutants other than toluene.

[0084] Table 1

[0085] Serial number Photocatalyst Degradation rate (%) 1 Comparative Example 1 29.8 2 Example 1 99.6 3 Example 2 96.5 4 Example 3 97.8 5 Example 4 99.3 6 Example 5 99.0 7 Example 6 97.3 8 Example 7 98.1 9 Example 8 98.5 10 Example 9 98.9 11 Example 10 97.5

[0086] Table 1 shows the degradation effects of the photocatalysts in Examples 1 to 10 and Comparative Example 1 on toluene. It can be seen that the Co / Cu-MOFs materials prepared in various embodiments of the present invention have a good degradation effect on toluene.

[0087] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. Application of CoCuO / CF material in photocatalytic oxidation degradation of volatile organic pollutants under visible light, characterized in that: The preparation method of the CoCuO / CF material comprises the following steps: dispersing a cobalt ion precursor and an organic ligand in an organic solvent, then adding copper foam, and performing a hydrothermal reaction, and washing, centrifuging and drying the product of the hydrothermal reaction to obtain a Co-loaded Cu-based MOFs material; Annealing the Co-loaded Cu-based MOFs material to obtain the CoCuO / CF material, wherein CF refers to foamed copper; The molar ratio of the cobalt ion precursor to the organic ligand is (0.5-3): (0.5-2); The cobalt ion precursor is cobalt nitrate hexahydrate or cobalt chloride hexahydrate; The organic ligand is terephthalic acid; The temperature of the hydrothermal reaction is 120-150°C, and the insulation time is 10-20 h; The annealing temperature is 200-400°C, the heating rate is 2-5°C / min, the holding time is 2-5 h, and the annealing atmosphere is air.

2. The use according to claim 1, characterized in that: The organic solvent includes at least one of N,N-dimethylformamide, methanol and ethanol.

3. The use according to claim 1, characterized in that: The volatile organic pollutants include toluene, chlorobenzene, ethyl acetate, acetone, tetrahydrofuran, cyclohexane or styrene.

Citation Information

Patent Citations

  • Preparation of foam metal-based monolithic catalyst and application of foam metal-based monolithic catalyst in photo-thermal degradation of VOCs (Volatile Organic Compounds)

    CN115845850A

  • Algae-shaped Co-MOF / copper hydroxide / foamy copper self-supporting electrode and preparation method and application thereof

    CN117802520A